Water Resource. Development in Jamnagar District, Gujarat, India - Sharma, K D (Annals of Arid Zone, 2016)
Regression models for rainfall-runoff-drainage basin area relationship, based on past 30 years' observations, have been developed for Jamnagar district in arid Gujarat, India. The runoff coefficient varies from 0.07 to 0.29 and the runoff efficiency decreases with the increasing area of drainage basin, since larger the basin, longer the flow paths and longer the opportunity time for rainwater infiltration. The probability of a severe drought by 2020 varies from 19 to 35% in various talukas in the district. The risk of failure of water control structures by a storm having 100 years as a return period is 63%. The study is useful in predicting the peak flows, water yield, rainwater infiltration, sediment transport and channel stability in the arid regions.